The Monitoring and Evaluation of a Multicountry Surveillance Study, the Severe Typhoid Fever in Africa Program. (30th October 2019) - Mogeni, Ondari D; Cruz Espinoza, Ligia María; Im, Justin; Panzner, Ursula; Toy, Trevor; Pak, Gi Deok; Haselbeck, Andrea; Ramani, Enusa; Schütt-Gerowitt, Heidi; Jacobs, Jan; Metila, Octavie Lunguya; Adewusi, Oluwafemi J; et al.
Abstract: Background: There is limited information on the best practices for monitoring multicountry epidemiological studies. Here, we describe the monitoring and evaluation procedures created for the multicountry Severe Typhoid Fever in Africa (SETA) study. Methods: Elements from the US Food and Drug Administration (FDA) and European Centre for Disease Prevention and Control (ECDC) recommendations on monitoring clinical trials and data quality, respectively were applied in the development of the SETA monitoring plan. The SETA core activities as well as the key data and activities required for the delivery of SETA outcomes were identified. With this information, a list of key monitorable indicators was developed using on-site and centralized monitoring methods, and a dedicated monitoring team was formed. The core activities were monitored on-site in each country at least twice per year and the SETA databases were monitored centrally as a collaborative effort between the International Vaccine Institute and study sites. Monthly reports were generated for key indicators and used to guide risk-based monitoring specific for each country. Results: Preliminary results show that monitoring activities have increased compliance with protocol and standard operating procedures. A reduction in blood culture contamination following monitoring field visits in two of the SETA countries are preliminary results of the impact of monitoring activities. Conclusions: Current monitoring recommendations applicable to clinical trials and routine surveillance systems can be adapted for monitoring epidemiological studies. Continued monitoring efforts ensure that the procedures are harmonized across sites. Flexibility, ongoing feedback, and team participation yield sustainable solutions.